Legal Protection for Victims of Traffic Accidents Due to Against The Law - Rafi Hidayahtullah Pakaya; Tutiek Retnowati (Faculty of Law, Merdeka University Surabaya, 2022)
The occurrence of a traffic accident is an act against the law that can result in harm to other people, violators can be sentenced in the form of payment of compensation either materially or immaterially to the victim and their heirs. According to Article 1365 of the Civil Code states